Depot Specific Differences and Insufficient Subcutaneous Adipose Tissue Angiogenesis in Human Obesity - Gealekman, Olga (2011)
BACKGROUND: Adipose tissue expands in response to excess caloric intake, but individuals prone to deposit visceral (VIS) instead of subcutaneous (SQ) adipose tissue have higher risk of metabolic disease. The role of angiogenesis in the expandability of human adipose tissue depots is unknown. The objective of this study was to measure angiogenesis in VIS and SQ adipose tissue, and to establish whether there is a relationship between obesity, metabolic status and the angiogenic properties of these depots. METHODS AND RESULTS: Angiogenic capacity was determined by quantifying capillary branch formation from human adipose tissue explants embedded in Matrigel, and capillary density was assessed by immunohistochemistry. SQ adipose tissue had a greater angiogenic capacity compared to VIS, even after normalization to its higher initial capillary density. Gene array analyses revealed significant differences in expression of angiogenic genes between depots, including an increased SQ expression of ANGPTL4, which is pro-angiogenic in an adipose tissue context. SQ capillary density and angiogenic capacity decreased with morbid obesity, and SQ, but not VIS, adipose tissue angiogenic capacity negatively correlated with insulin sensitivity. CONCLUSIONS: These data imply that SQ adipose tissue has a higher capacity to expand its capillary network compared to VIS, but this capacity decreases with morbid obesity. The decrease correlates with insulin resistance, suggesting that impairment of SQ adipose tissue angiogenesis may contribute to metabolic disease pathogenesis.